2003
DOI: 10.1021/op034062w
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Development of LB71350

Abstract: An efficient synthesis of the HIV-1 protease inhibitor LB71350 (1) is described. High diastereoselective epoxidation of the cisallylic carbamate fragment of (5S)-[N-(benzyloxycarbonyl)-amino]-N-[2-methyl-(1R)-[(phenyl)carbonyl]-propyl]-6-phenylhex-(Z)-enamide (16) and one-pot preparation of N-[(1-methylethoxy)carbonyl]-3-(methylsulfonyl)-L-valine (4) are the key features of the synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…Figure provides a working model of the low energy conformers of the cis - and trans -ketimines influencing facial selectivity during the addition of hydrogen to N -α-MBA ketimines. The models are consistent with the major amine diastereomer formed (either S , S or R , R depending on the starting enantiomer of α-MBA) and are in accordance with the well-established concept of allylic 1,3-strain and earlier proposed models. 15c,i Contrary to this model, it has been previously suggested that the reductive amination of an α-keto ester with α-MBA may involve a rotamer (about the nitrogen-benzylic carbon bond) with the phenyl ring of α-MBA coplanar to the ketimine double bond . The idea is appealing because of the well described affinity of π bonds for heterogeneous hydrogenation catalyst surfaces, but examination of the two possible trans -ketimine rotamers (not shown), with a coplanar phenyl group relative to the ketimine double bond, shows one suffering from high allylic 1,3-strain 35 (prominent phenyl group steric crowding with the methyl group attached to the carbonyl carbon of the ketimine) while the other rotamer is less encumbered (1,2-strain from the electron pair of the ketimine nitrogen and one of the ortho hydrogens of the phenyl ring) but leads to the formation of the wrong amine product diastereomer.…”
Section: Resultssupporting
confidence: 86%
“…Figure provides a working model of the low energy conformers of the cis - and trans -ketimines influencing facial selectivity during the addition of hydrogen to N -α-MBA ketimines. The models are consistent with the major amine diastereomer formed (either S , S or R , R depending on the starting enantiomer of α-MBA) and are in accordance with the well-established concept of allylic 1,3-strain and earlier proposed models. 15c,i Contrary to this model, it has been previously suggested that the reductive amination of an α-keto ester with α-MBA may involve a rotamer (about the nitrogen-benzylic carbon bond) with the phenyl ring of α-MBA coplanar to the ketimine double bond . The idea is appealing because of the well described affinity of π bonds for heterogeneous hydrogenation catalyst surfaces, but examination of the two possible trans -ketimine rotamers (not shown), with a coplanar phenyl group relative to the ketimine double bond, shows one suffering from high allylic 1,3-strain 35 (prominent phenyl group steric crowding with the methyl group attached to the carbonyl carbon of the ketimine) while the other rotamer is less encumbered (1,2-strain from the electron pair of the ketimine nitrogen and one of the ortho hydrogens of the phenyl ring) but leads to the formation of the wrong amine product diastereomer.…”
Section: Resultssupporting
confidence: 86%
“…Chiral N-protected α-amino ketones are useful precursors to many biologically active compounds including chiral α-amino alcohols, pharmaceutically important chiral heterocycles, , and diamines. 1c, Preparations of α-amino aliphatic ketones and α-amino aryl ketones have been thoroughly investigated, but much less attention has been directed toward the synthesis of α-aminoalkyl heterocyclic ketones and to our knowledge, no general method has been reported. Previous syntheses of chiral α-amino ketones utilized N - protected α-amino acids, esters, and amides (i) with organometallic reagents for nucleophilic substitution 6 or (ii) with AlCl 3 for Friedel−Crafts acylations .…”
Section: Introductionmentioning
confidence: 99%
“…24–27 In the presence of a base, namely Et 3 N, NMM or N -methylpiperidine, carboxylic acids are first transformed into the corresponding mixed anhydrides using acid chlorides, such as pivaloyl chloride (PivCl) 28–41 or isobutyl chloroformate (IBCF). 42–51 The advantages of PivCl for scale-up include its relatively low cost, wide availability, and nontoxic pivalic acid as a byproduct after aqueous workup. Recently, we questioned whether inexpensive and easy to handle pivaloyl anhydride (Piv 2 O) might be applied for the generation of pivaloyl mixed anhydrides via carboxyl exchange 52–59 to avoid the use of an additional base and enable a more sustainable amine condensation method.…”
Section: Introductionmentioning
confidence: 99%